Advanced stellar astrophysics - Rose, William K. 1935- (Cambridge University Press, 1998)
In the last few decades, remarkable progress has been made in understanding stars. This graduate-level 1998 textbook provides a systematic, self-contained and lucid introduction to the physical processes and fundamental equations underlying all aspects of stellar astrophysics. The volume provides authoritative astronomical discussions as well as rigorous mathematical derivations and illuminating explanations of the physical concepts involved. In addition to traditional topics such as stellar interiors and atmospheres, the reader is introduced to stellar winds, mass accretion, nuclear astrophysics, weak interactions, novae, supernovae, pulsars, neutron stars and black holes. A concise introduction to general relativity is also included. At the end of each chapter, exercises and helpful hints are provided to test and develop the understanding of the student. This advanced textbook on stellar astrophysics provides a thorough introduction for graduate students and a review for researchers.